Look where we live! a first book of community building - Ritchie, Scot 1954- (Toronto: Kids Can Press, 2015)
In this book, five young friends -- Nick, Yulee, Pedro, Sally and Martin -- spend the day traveling around their neighborhood and participating in activities designed to raise money for their local library. Along the way, they learn about the people and places that make up their community and what it means to be a part of one
Keywords: Communities / Juvenile literature; Community life / Juvenile literature; Communities; Community life